Eksplorasi Etnomatematika pada Ragam Motif Batik Gumelem Banjarnegara - Aprilina, Amanda; Faza, Aruni; Listyani, Erlin; Kusuma, Anggun Badu (Pendidikan Matematika FKIP Universitas Mataram, 2025)
This study aims to explore the mathematical aspects of various Gumelem batik motifs typical of Banjarnegara Regency. The background of this study is the lack of mathematical studies that focus on this batik. The method used is descriptive qualitative with an ethnographic approach through direct observation, documentation, and in-depth interviews with batik artisans. Data analysis was carried out by identifying mathematical elements such as plane geometry, similarity, congruence, geometric transformations, algebraic principles, and number sequence patterns. The results show that Gumelem batik motifs contain various mathematical components. The Watu Pecah motif contains the concepts of triangles, rhombuses, and congruence. The Gedong Kosongan Coletan motif depicts similarity and the Two-Variable Linear Equation System (SPLDV). The Kawung Plangkah Merak motif includes dilation and rotation, while the Babon Angrem motif applies reflection and the Dieng Temple motif shows translation. In addition, the Udan Liris motif depicts the concept of number sequences. This study confirms the great potential of Gumelem batik as a local culture-based mathematics learning medium (ethnomathematics) that is relevant to local wisdom.